2018
DOI: 10.1002/anie.201804446
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Synthesis of Allenes by Point‐to‐Axial Chirality Transfer

Abstract: An enantiodivergent method for the synthesis of multiply substituted allenes is described. Highly enantioenriched, point‐chiral boronic esters were synthesized by homologation of α‐seleno alkenyl boronic esters with lithiated carbamates and eliminated to form axially chiral allene products. By employing either oxidative or alkylative conditions, both syn and anti elimination could be achieved with complete stereospecificity. The process enables the synthesis of either M or P allenes from a single isomer of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 80 publications
0
14
0
1
Order By: Relevance
“…Sun and co‐workers disclosed in 2017 the synthesis of chiral tetrasubstituted allenes from racemic propargylic alcohols by asymmetric trapping of intermediate propargylic cations, which were generated with a chiral Brønsted acid . Recently, Aggarwal and co‐workers presented an enantiodivergent method to access highly substituted allenes, including tetrasubstituted allenes, by point‐to‐axial chirality transfer with chiral allyl boronic esters as substrates . The same group also reported an elegant stereospecific deborylative γ‐arylation of enantioenriched propargylic boronic pinacol esters with aryl iodides, affording tetrasubstituted allenes by metal catalysis (Scheme c) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun and co‐workers disclosed in 2017 the synthesis of chiral tetrasubstituted allenes from racemic propargylic alcohols by asymmetric trapping of intermediate propargylic cations, which were generated with a chiral Brønsted acid . Recently, Aggarwal and co‐workers presented an enantiodivergent method to access highly substituted allenes, including tetrasubstituted allenes, by point‐to‐axial chirality transfer with chiral allyl boronic esters as substrates . The same group also reported an elegant stereospecific deborylative γ‐arylation of enantioenriched propargylic boronic pinacol esters with aryl iodides, affording tetrasubstituted allenes by metal catalysis (Scheme c) .…”
Section: Methodsmentioning
confidence: 99%
“…[11] Sun and co-workers disclosed in 2017 the synthesis of chiral tetrasubstituted allenes from racemic propargylic alcohols by asymmetric trapping of intermediate propargylic cations,w hich were generated with achiral Brønsted acid. [13] Thesame group also reported an elegant stereospecific deborylative g-arylation of enantioenriched propargylic boronic pinacol esters with aryl iodides,a ffording tetrasubstituted allenes by metal catalysis (Scheme 1c). [13] Thesame group also reported an elegant stereospecific deborylative g-arylation of enantioenriched propargylic boronic pinacol esters with aryl iodides,a ffording tetrasubstituted allenes by metal catalysis (Scheme 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Aggarwal reported am odified Zweifel-type olefination proceeding through an ovel syn elimination process (Scheme 9). [27] This was achieved by employing PhSeCl as the electrophile for the selenation of alkenyl boronates 43,which led to b-selenoboronic esters 46 through the stereospecific 1,2-migration ring-opening of seleniranium intermediates 45.I tw as found that m-CPBAw as able to chemoselectively oxidise the selenide to give selenoxide intermediate 47,which underwent syn elimination to provide Scheme 6. Synthesis of a-heteroatom-substituted alkenes by Zweifel olefination and application to the synthesis of baulamycins Aand B. PMB = 4-methoxybenzyl.…”
Section: Sulfur and Selenium-based Electrophilesmentioning
confidence: 99%
“…[12] Vork urzem stellte Aggarwal eine enantiodivergente Methode zum Aufbau von hochsubstituierten Allenen durch die Übertragung von Punkt-zu-axialer Chiralitätv or, einschließlich Beispiele von chiralen tetrasubstituierten Allenen unter Verwendung chiraler Allylboronsäureester als Substrate. [13] Dieselbe Gruppe berichtete auch über eine elegante stereospezifische deborylierende g-Arylierung von enantiomerenangereicherten Propargylborpinacolestern mit Aryliodiden, um tetrasubstituierte Allene mittels Metallkatalyse aufzubauen (Schema 1c). [14] In der vorliegenden Arbeit stellen wir unsere ersten Ergebnisse der hoch stereospezifischen decarboxylierenden g-Arylierung von a,a-disubstituierten b,g-Alkinsäuren mit Aryliodiden mittels Pd-Katalyse fürd ie Herstellung chiraler tetrasubstituierter Allene vor (Schema 1d).…”
unclassified